Diseño y aplicación de un programa de capacitación para evitar el consumo de drogas y alcohol dirigido a los estudiantes de los décimos años de educación básica del Instituto Técnico Industrial “Ramón Barba Naranjo” en el periodo 2012 – 2013 - Bastidas Martínez, Gabriela de la Mercedes (2015)
The research called “A training program Design and Implementation in order to prevent drug and alcohol abuse in tenth grade of Basic Education at “Ramón Barba Naranjo " Industrial Technical Institute". The study characteristics are those of a qualitative research on the research method. The research design was developed in four steps: Assessment, Planning, Implementation and Evaluation. For this study, students and a teacher participate in it. An interview was applied as data collection instrument. A categorization triangulation was applied in order to make information analysis. This action let a right theorizing. The results allowed us to conclude that the institutional problems are the drug use risks in the daily routine. So that, the preventive strategies will provide teenager tools to achieve integral training and the ability to solve their problems with creative according his/her real way. The student addresses this problem by generating of prevention forms.